The roles of the heads of elementary teacher education institutions in the Philippines and their implications for Nepal - Mallik, Birendra Kumar 1937- (s.n.], 1967)
This study analyzed the administrative and supervisory responsibilities of the heads of primary teacher education institutions in the Philippines in order to find out the different administrative and supervisory activities of the heads, the way they perform these activities and the differences in their administrative and supervisory practices to deduce implications for the the improvement of teacher education in Nepal.